2008
DOI: 10.1121/1.2913251
|View full text |Cite
|
Sign up to set email alerts
|

Consonant confusions in white noise

Abstract: The classic [MN55] confusion matrix experiment (16 consonants, white noise masker) was repeated by using computerized procedures, similar to those of Phatak and Allen (2007). ["Consonant and vowel confusions in speech-weighted noise," J. Acoust. Soc. Am. 121, 2312-2316]. The consonant scores in white noise can be categorized in three sets: low-error set [/m/, /n/], average-error set [/p/, /t/, /k/, /s/, /[please see text]/, /d/, /g/, /z/, /Z/], and high-error set /f/theta/b/, /v/, /E/,/theta/]. The consonant c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
99
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(114 citation statements)
references
References 23 publications
14
99
1
Order By: Relevance
“…3 indicated that any considered difference in the stimuli produced a measurable effect. The observed perceptual variability across talkers is well established in the related literature (e.g., Phatak et al 2008); the equally large variability within talkers had not yet been demonstrated. Most remarkably, even a 100-ms time shift in the white maskingnoise waveform induced significant perceptual variability, indicating that "steadystate" masking noise should not be considered steady over time in the context of consonant cues.…”
Section: Summary and Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…3 indicated that any considered difference in the stimuli produced a measurable effect. The observed perceptual variability across talkers is well established in the related literature (e.g., Phatak et al 2008); the equally large variability within talkers had not yet been demonstrated. Most remarkably, even a 100-ms time shift in the white maskingnoise waveform induced significant perceptual variability, indicating that "steadystate" masking noise should not be considered steady over time in the context of consonant cues.…”
Section: Summary and Discussionsupporting
confidence: 49%
“…Phatak and Allen (2007) measured consonant perception in speech-weighted noise and demonstrated noise-type induced perceptual differences to the Miller and Nicely (1955) data. In following studies, perceptual differences across different speech tokens of the same phonetic identity came more into focus (e.g., Phatak et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, NH listeners show the same confusion group in the presence of a white noise masker ͑Miller and Nicely, 1955; Phatak et al, 2008͒. This is because white noise masks higher frequencies more than speech-weighted noise at a given SNR.…”
Section: E Consonant Confusionsmentioning
confidence: 95%
“…It has been shown that NH listeners demonstrate a wide range of performance across different consonants presented in noise ͑Phatak and Phatak et al, 2008͒, and it is likely that HI listeners would also exhibit a variance in performance across the same consonants. A quantitative comparison of recognition performances for individual consonants is necessary to determine whether the loss of performance for HI listeners is consonant-dependent.…”
Section: Introductionmentioning
confidence: 99%
“…All the sounds were from the LDC2005S22 corpus ("Articulation Index Corpus" provided by the Linguistic Data Consortium, University of Pennsylvania). Data from Phatak et al (2008) verified that these utterances had 0% recognition error at and above þ12 dB SNR. A total of 14 different talkers were used, two of whom had spent some part of their childhood outside the US while others had early training in a language other than English (Fousek et al, 2004).…”
Section: A Stimulimentioning
confidence: 99%